2016
DOI: 10.1093/cid/ciw745
|View full text |Cite
|
Sign up to set email alerts
|

Increased Antiviral Treatment Among Hospitalized Children and Adults With Laboratory-Confirmed Influenza, 2010–2015

Abstract: Using population-based surveillance data, we analyzed antiviral treatment among hospitalized patients with laboratory-confirmed influenza. Treatment increased after the influenza A(H1N1) 2009 pandemic from 72% in 2010–2011 to 89% in 2014–2015 (P < .001). Overall, treatment was higher in adults (86%) than in children (72%); only 56% of cases received antivirals on the day of admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…Late antiviral treatment also appears to be an important confounder between obesity and influenza severity, as the likelihood of severe disease increased among obese individuals after adjustment for treatment in all models. These findings add to previous observations of the connection between antiviral treatment and obesity; a 2016 paper examined antiviral treatment among hospitalized patients from 2010 to 2015 and found that individuals with high risk conditions, including morbid obesity, were significantly more likely than non‐obese individuals to receive antivirals; however, the 2016 study did not evaluate timing of therapy …”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Late antiviral treatment also appears to be an important confounder between obesity and influenza severity, as the likelihood of severe disease increased among obese individuals after adjustment for treatment in all models. These findings add to previous observations of the connection between antiviral treatment and obesity; a 2016 paper examined antiviral treatment among hospitalized patients from 2010 to 2015 and found that individuals with high risk conditions, including morbid obesity, were significantly more likely than non‐obese individuals to receive antivirals; however, the 2016 study did not evaluate timing of therapy …”
Section: Discussionmentioning
confidence: 61%
“…These findings add to previous observations of the connection between antiviral treatment and obesity; a 2016 paper examined antiviral treatment among hospitalized patients from 2010 to 2015 and found that individuals with high risk conditions, including morbid obesity, were significantly more likely than non-obese individuals to receive antivirals; however, the 2016 study did not evaluate timing of therapy. 23 This study took place at hospitals in Detroit, Michigan, a city with high levels of obesity and poverty. 24 As expected in hospitals in an underserved area, many participants had self-reported poor health in addition to the need for special medical equipment and physical, mental, or emotional limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of .30 000 admissions due to influenza (including .6000 children) revealed similar rates of timely administration of anti-influenza medications regardless of duration of illness preceding hospitalization. 17 Differences in care pathways between individual hospitals were unavailable from the database and may have accounted for differences in our outcomes. However, we found that differences in treating hospitals accounted for 0% to 2.3% of variance in all outcomes, which suggests any variations due to hospital-level factors, such as care pathways, did not have significant influence on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Most children hospitalized with influenza, however, do not receive anti-influenza medications in a timely fashion. 17,18 Furthermore, evidence regarding efficacy of anti-influenza medications among CMC is limited.…”
mentioning
confidence: 99%